2023
DOI: 10.1001/jamanetworkopen.2023.5847
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Therapy Costs and Downstream Cost Consequences of iBASIS–Video Interaction to Promote Positive Parenting Intervention vs Usual Care Among Children Displaying Early Behavioral Signs of Autism in Australia

Abstract: ImportanceThe growing global prevalence of autism spectrum disorder (ASD) is associated with increasing costs for support services. Ascertaining the effects of a successful preemptive intervention for infants showing early behavioral signs of autism on human services budgets is highly policy relevant.ObjectiveTo estimate the net cost impact of the iBASIS–Video Interaction to Promote Positive Parenting (iBASIS-VIPP) intervention on the Australian government.Design, Setting, and ParticipantsInfants (aged 12 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…Early and intensive language therapy has the greatest promise of signi cantly improving outcomes 33 . More speci cally, available data suggests that for every $1 invested in supporting neurodivergent infants and their parents early, the country could save at least $3 down the track 34 . Other studies have also demonstrated that early intervention, particularly language exercises, signi cantly improves children's outcomes, and is the greatest tool available to reduce the societal cost of caring for autistic individuals [35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…Early and intensive language therapy has the greatest promise of signi cantly improving outcomes 33 . More speci cally, available data suggests that for every $1 invested in supporting neurodivergent infants and their parents early, the country could save at least $3 down the track 34 . Other studies have also demonstrated that early intervention, particularly language exercises, signi cantly improves children's outcomes, and is the greatest tool available to reduce the societal cost of caring for autistic individuals [35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…In the Original Investigation titled “Estimated Therapy Costs and Downstream Cost Consequences of iBASIS–Video Interaction to Promote Positive Parenting Intervention vs Usual Care Among Children Displaying Early Behavioral Signs of Autism in Australia,” 1 published April 5, 2023, the conflict of interest disclosure for Dr Whitehouse incorrectly listed him as a joint copyright holder of the iBASIS–Video Interaction to Promote Positive Parenting (iBASIS-VIPP) intervention. Dr Whitehouse is employed by the organization that holds the patent.…”
mentioning
confidence: 99%